The Relationship between Nutritional Status (Body Mass Index) of Three Pregnant Women with Estimated Fetal Weight - Sumarni Sumarni; Nour Sriyanah; Andi Ria Metasari; Susilawati Susilawati; Ermawati Ermawati (Proceedings of the International Conference on Nursing and Health Sciences, 2022)
Many third trimester pregnant women experience problems related to nutritional status that affect the growth and development of their fetus. This study aims to determine the relationship between Body Mass Index (BMI) and Estimated Fetal Weight (TBJ). This research method uses an analytical survey method.Populationi in this study were third trimester pregnant women.Amount Samples were 72 third trimester pregnant women selected by accidental sampling who met the inclusion criteria. Using the Chi-Square test, the results obtained were p=0.004 (p<0.05). This shows that there is a significant relationship between body mass index and estimated fetal weight at UPT Puskesmas Watampone. The final conclusion of the researchers is that mothers pay more attention to fulfilling nutrition during pregnancy to prevent births with abnormal baby weights.